Coming through my eyes - Tan, Christopher, 1972- (Petaling Jaya, Selangor, Malaysia : A2 Communications, 2010)
Social life and customs of the Malaysian society.
Keywords: Malaysia -- Social life and customs; Malaysia -- Politics and government